Peningkatan Kreativitas Menulis Cerpen Siswa MA Nurul Ichsan Melalui Penerapan AI dan Metode Mind Mapping: Increasing the Short Story Writing Creativity of MA Nurul Ichsan Students Through the Application of AI and Mind Mapping Methods - Hanan; Moh. Ahsan Shohifur Rizal; Kholik (Universitas Nusantara PGRI Kediri, 2024)
This action research investigated the impact of AI and mind mapping techniques on enhancing student creativity in short story writing. Recognizing the significance of short story writing in language skill development, the study addressed the challenge of ineffective teaching methods in literature education. Employing a qualitative approach with action research methodology, the study spanned two cycles. The first involved initial data collection through interviews and a baseline short story writing test. The second cycle introduced AI and mind mapping, followed by a subsequent writing test. Results demonstrated a significant increase in student creativity through mind mapping. This technique facilitated idea generation and conceptualization, leading to more imaginative and coherent narratives, reflected in a 17.22% improvement. Furthermore, integrating AI and mind maps as learning tools heightened student motivation, engagement, and enthusiasm. This enhanced involvement fostered deeper comprehension of the material, consequently improving the overall effectiveness of the learning process. The study highlights the potential of these innovative methods in cultivating creativity and improving short story writing skills.